Dynamic sustainabilities : technology, environment, social justice - Leach, Melissa; Scoones, Ian.; Stirling, Andy. (London ; Washington, DC : Earthscan, 2010)
Introducing a new pathways approach for understanding and responding to sustainability challenges, this title explores practical ways forward for building pathways to sustainability.
Sustainability challenges in a dynamic world -- Dynamic systems: environment and development challenges -- Pathways to sustainability: responding to dynamic contexts -- Governance in a dynamic world -- Opening up, broadening out: empowering designs for sustainability -- An alternative politics for sustainability -- Towards pathways to sustainability.
Includes bibliographical references and index.
Keywords: Sustainable development; Economic development -- Environmental aspects; Poverty; Social justice